Discovery of MK‐8742: An HCV NS5A Inhibitor with Broad Genotype Activity. Issue 12 (14th October 2013) - Coburn, Craig A.; Meinke, Peter T.; Chang, Wei; Fandozzi, Christine M.; Graham, Donald J.; Hu, Bin; Huang, Qian; Kargman, Stacia; Kozlowski, Joseph; Liu, Rong; McCauley, John A.; Nomeir, Amin A.; et al.
Abstract The NS5A protein plays a critical role in the replication of HCV and has been the focus of numerous research efforts over the past few years. NS5A inhibitors have shown impressive in vitro potency profiles in HCV replicon assays, making them attractive components for inclusion in all oral combination regimens. Early work in the NS5A arena led to the discovery of our first clinical candidate, MK‐4882 [2‐((S)‐pyrrolidin‐2‐yl)‐5‐(2‐(4‐(5‐((S)‐pyrrolidin‐2‐yl)‐1H‐imidazol‐2‐yl)phenyl)benzofuran‐5‐yl)‐1H‐imidazole]. While preclinical proof‐of‐concept studies in HCV‐infected chimpanzees harboring chronic genotype 1 infections resulted in significant decreases in viral load after both single‐ and multiple‐dose treatments, viral breakthrough proved to be a concern, thus necessitating the development of compounds with increased potency against a number of genotypes and NS5A resistance mutations. Modification of the MK‐4882 core scaffold by introduction of a cyclic constraint afforded a series of tetracyclic inhibitors, which showed improved virologic profiles. Herein we describe the research efforts that led to the discovery of MK‐8742, a tetracyclic indole‐based NS5A inhibitor, which is currently in phase 2b clinical trials as part of an all‐oral, interferon‐free regimen for the treatment of HCV infection.